2009
DOI: 10.1007/978-1-59745-561-9_29
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of an Oncolytic HSV Vector Containing a Fusogenic Glycoprotein and Prodrug Activation for Enhanced Local Tumor Control

Abstract: A large number of oncolytic viral vectors are currently under clinical development for cancer therapy. Herpes simplex virus type 1 (HSV-1) has demonstrated particular promise in this field, showing genetically engineered selective tumor replication and cytotoxicity in a wide variety of tumor types, without damaging healthy tissues. Enhanced activity has been observed when a range of therapeutic genes has been inserted into various oncolytic HSV genomes. Here, we discuss methods used to develop and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A range of transgene inserts have been evaluated, including suicide genes (Chase et al, 1998;Aghi et al, 1999;Nakamura et al, 2001;Guffey et al, 2007), or those expressing antiangiogenic (Liu et al, 2006;Goodwin et al, 2012;Yoo et al, 2012), apoptotic (Han et al, 2007;Prabhakar et al, 2010), fusogenic (Nakamori et al, 2004;Simpson et al, 2009;Takaoka et al, 2011), and immunomodulatory proteins (Andreansky et al, 1998;Liu et al, 2003;Parker et al, 2005;Walker et al, 2011). Our group has focused on oHSV that express immunostimulatory cytokines (Andreansky et al, 1998;Parker et al, 2000;Hellums et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A range of transgene inserts have been evaluated, including suicide genes (Chase et al, 1998;Aghi et al, 1999;Nakamura et al, 2001;Guffey et al, 2007), or those expressing antiangiogenic (Liu et al, 2006;Goodwin et al, 2012;Yoo et al, 2012), apoptotic (Han et al, 2007;Prabhakar et al, 2010), fusogenic (Nakamori et al, 2004;Simpson et al, 2009;Takaoka et al, 2011), and immunomodulatory proteins (Andreansky et al, 1998;Liu et al, 2003;Parker et al, 2005;Walker et al, 2011). Our group has focused on oHSV that express immunostimulatory cytokines (Andreansky et al, 1998;Parker et al, 2000;Hellums et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One such fusogenic virus is the recombinant HSV-GALV,116, 117, 118 which combines the oncolytic HSV backbone with the gibbon ape leukemia virus (GALV) fusion protein. Although GALV has poor oncolytic potential alone, the virus is hyperfusogenic, and insertion of its F protein into oncolytic HSV has been reported to generate a fusogenic construct with significantly increased oncolytic potential 119 .…”
Section: Main Textmentioning
confidence: 99%
“…To this purpose, it has been recently demonstrated that incorporation of cell membrane fusion capability into an oncolytic HSV can significantly increase the antitumor potency of the virus [217-219]. These oncolytic HSVs were constructed by different methods: (i) screening for the syncytial phenotype after random mutation of a well-established oncolytic HSV (to obtain Fu-10); (ii) insertion of the gene encoding the hyperfusogenic membrane glycoprotein of gibbon ape leukemia virus (GALV.fus) into the genome of an oncolytic HSV (to generate Synco-2); (iii) incorporation of both of these two membrane fusion mechanisms into a single oncolytic HSV (to generate Synco-2D); and (iv) combined expression of GALV with a highly potent prodrug activation gene (yeast cytosine deaminase/uracil phosphoribosyl-transferase fusion [Fcy::Fur]) [220]. These vectors have been tested for their antitumor activity against liver, breast, ovarian and metastatic prostate cancers showing a significant increase in viral oncolysis; this may lead to an enhanced clinical performance, especially in the late stage cancer patients.…”
Section: Hsv-1 Based Vectors For Cancer Gene Therapymentioning
confidence: 99%